Development of metal-organic framework (MOF) decorated graphene oxide nanoplatforms for anti-corrosion epoxy coatings. (May 2020) - Ramezanzadeh, Mohammad; Ramezanzadeh, Bahram; Mahdavian, Mohammad; Bahlakeh, Ghasem
Abstract: In this study, a novel corrosion protective coating with an excellent barrier, and superior active anti-corrosion characteristics was constructed through a one-pot synthesis method of zeolitic imidazolate framework-8 (ZIF-8) on the graphene oxide sheets. Experimental results proved the successfully synthesize of GO@ZIF-8 particles with a 79% improvement of the specific surface area compared with the neat GO. A corrosion inhibition efficiency of about 79% was recorded for the steel sample immersed in the NaCl solution containing GO@ZIF-8 particles extract by the polarization test, proving the active inhibition properties of GO@ZIF-8 particles. The low-frequency impedance (| Z |10 mHz ) values greater than 10 10  Ω cm 2 were recorded by EIS analysis for the GO@ZIF-8/epoxy coating at all immersion times, indicating the superior barrier anti-corrosion properties of this coating. The pull-off and cathodic delamination tests revealed about 73% and 60% improvements of the epoxy coating cathodic delamination resistance and wet adhesion strength, respectively, in the presence of GO@ZIF-8 particles in comparison with the neat epoxy sample. The EIS outcome revealed a 70% improvement in the corrosion resistance of the GO@ZIF-8 loaded epoxy composites with an artificial defect after 72 h immersion than the neat epoxy sample, indicating the good smart inhibition activity for this sample. Graphical abstract: Image 1